2007
DOI: 10.1152/ajpheart.00985.2006
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium attenuates isoproterenol-induced acute cardiac dysfunction and β-adrenergic desensitization

Abstract: nervous activation is a crucial compensatory mechanism in heart failure. However, excess catecholamine may induce cardiac dysfunction and ␤-adrenergic desensitization. Although magnesium is known to be a cardioprotective agent, its beneficial effects on acute cardiac dysfunction remain to be elucidated. We examined the effects of magnesium on left ventricular (LV) dysfunction induced by a large dose of isoproterenol in dogs. Sixteen anesthetized dogs underwent a continuous infusion of isoproterenol (1 g ⅐ kg Ϫ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
2
16
0
1
Order By: Relevance
“…These results are also not in disagreement with those in a canine wedge preparation by Wilson et al (45), who used a different model to show that the action potential and Ca 2ϩ alternans in the heart failure hearts occurred at slower heart rates compared with normal hearts. Furthermore, the mechanisms of ␤-adrenergic stimulation by isoproterenol involve an additional influx of Ca 2ϩ into myocytes, overloading the Ca 2ϩ -handling cascades, which are chronically impaired in heart failure (6,12). Thus, Ca 2ϩ alternans and impaired Ca 2ϩ handling could be the driving force behind the TWA observed after the injection of isoproterenol in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…These results are also not in disagreement with those in a canine wedge preparation by Wilson et al (45), who used a different model to show that the action potential and Ca 2ϩ alternans in the heart failure hearts occurred at slower heart rates compared with normal hearts. Furthermore, the mechanisms of ␤-adrenergic stimulation by isoproterenol involve an additional influx of Ca 2ϩ into myocytes, overloading the Ca 2ϩ -handling cascades, which are chronically impaired in heart failure (6,12). Thus, Ca 2ϩ alternans and impaired Ca 2ϩ handling could be the driving force behind the TWA observed after the injection of isoproterenol in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…In an earlier study, Jin et al . reported that a continuous infusion of a large dose of IsoP (1 µg/kg/min) in dogs induced acute left ventricular dysfunction with leakage of myocardial enzymes and contractile proteins indicating myocardial damage, within 2 h of administration, as well as the release of atrial natriuretic peptide. Interestingly, subcutaneous administration of IsoP at an interval of 24 h for 2 days was shown to decrease the activities of Na + /K + ATPase and Mg 2+ ATPase, whereas the activity of Ca 2+ ATPase was increased in IsoP‐treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Because the calcitropic hormones, parathyroid hormone (PTH) and vitamin D, potentiate Ca 2+ overloading and ATP loss, they sensitize cardiomyocytes to catecholamine-induced necrosis [22]. This contrasts to Ca 2+ channel blockers, cations (e.g., Zn 2+ ) which compete with Ca 2+ entry, or β 1 adrenergic receptor antagonists, each of which were cardioprotective in response to catecholamine treatment of rats using isoproterenol (Isop) [45,36,75,16,76]. The multidisciplinary team of talented investigators from the Institute contributed importantly to this “new principle in cardiac pathophysiology” [21].…”
Section: Mitochondriocentric Pathway To Nonischemic Cardiomyocyte Necmentioning
confidence: 99%